Geophysical and Geological investigation of the Delga proposed Dam Site, Qala Diza, Sulaimani City, Kurdistan Region, NE-Iraq - Aziz, Bakhtiar Q.; Ali, Salahalddin S.; Karim, Kamal H. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The use of two geophysical methods and geological study in the investigation of the geological setting is aimed at evaluating the feasibility of the area for establishing a dam foundation and reservoir. 2D resistivity tomography was conducted on abutments while GPR was used on the river terraces in the trough of the valley. The framework and mutual relations of the geophysics, stratigraphy, lithology, structure, hydrologeology and geotechnique are used to study feasibility of a segment of river valley for dam building. The study is aided by detail and uptodate geological maps and geological cross sections which are all base on field data and geophysical measurements. This proposed dam is located at the southeast Delga village and about 20.0 km upstream of Dokan reservoir on little Zab River and about 19.5 km from the Iraqi-Iranian border. The dam site and surround areas are located in the Imbricated Zone which characterized by southwest overturning of the folds. The dam site is located on one of the overturned syncline in which Shiranish and Kometan Formations are exposed and the foundation and abutments of the dam are located on latter formation. The trend of the dam axis is N80W and the dip of the strata of the Kometan Formation is nearly parallel to the dam axis. This structure relation with dam axis improves water tightness and stability of the dam abutments against sliding and collapse. The 2D resistivity tomography and GPR survey showed that there are underground week zones (cavern and fractured zones) in restricted limited area. The site is water tight as the river descended inside fresh Kometan and Shiranish Formation.